Glosa do postanowienia SN z dnia 3 sierpnia 2023 r., I CSK 5377/22. Moment powstania uzasadnienia wyroku - Rzewuski, Maciej (PRAWO i WIĘŹ, 2024)
The subject of the paper is the analysis of the opinion of the Supreme Court expressed on the basis of the examination of a specific cassation case. The opinion expressed touches on one of the most important issues of civil procedural law, i.e. when a court decision is justified. This question concerns many serious issues related to the citizen’s right to court and the possibility of appealing against unfavorable court decisions.